Tagore and nationalism - Quayum, Mohammad Abdul (The Daily Star, Bangladesh, 2013)
An article that examines Tagore's perception of the philosophy of nationalism and why he was opposed to it at a time when nationalism was the most universally accepted political institution in the world -- East and West.